Measuring phonon dephasing with ultrafast pulses using Raman spectral interference - Waldermann, F; Sussman, B; Nunn, J; Lorenz, V; Lee, K; Surmacz, K; Lee, K; Jaksch, D; Walmsley, I; Spizziri, P; Olivero, P; Prawer, S (2008)
A technique to measure the decoherence time of optical phonons in a solid is presented. Phonons are excited with a pair of time-delayed 80 fs near infrared pulses via spontaneous transient Raman scattering. The spectral fringe visibility of the resulting Raman pulse pair, as a function of time delay, is used to measure the phonon dephasing time. The method avoids the need to use either narrow band or few femtosecond pulses and is useful for low phonon excitations. The dephasing time of phonons created in bulk diamond is measured to be τ=6.8 ps (Δν=1.56 cm-1). ©2008 The American Physical Society.